Use Of Online Communication Media “Google Classroom” In Lecture Activities During The Covid-19 Pandemic - Meri Suarti; Sri Narti; Asnawati Asnawati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
During the Covid-19 pandemic, lectures at Unived Bengkulu were conducted online. One of the media used to facilitate online communication during lectures is google classroom. Lecturing through google classroom is a new innovation for lecturers and students who previously lectured face to face and then conducted online. To find out the use of online communication media, google classroom in lectures at Unived Bengkulu during the Covid-19 pandemic, the author uses the characteristics of innovation from Everett M. Rogers which has five characteristics that can affect the level of use of an innovation, namely relative advantage, compatibility, complexity, trialability, and observability. This research uses descriptive qualitative methods with data collection techniques of observation, interviews, and documentation. The technique of determining informants using purposive sampling, the informants consisted of three lecturers and nine students. The results of the study state that based on the characteristics of its relative advantage, google classroom is a flexible, simple and efficient medium. Based on the characteristics of compatibility, Google Classroom is considered suitable for use during this pandemic, because Google Classroom can be accessed anywhere and anytime that is connected to the internet. Complexity is felt in difficult networks, especially in rural areas. Based on observations during the trial in the early semester, this media can be reused in the following semester. The use of online communication media google classroom in lectures during the Covid-19 pandemic at Dehasen Bengkulu University ran smoothly and was suitable to be applied during the Covid-19 period, even though constraints with network, but this could be overcome because it had a deadline given by the lecturer.